ANALISIS IMPLEMENTASI E-FILING TERHADAP KEPATUHAN WAJIB PAJAK ORANG PRIBADI - Ratna, Ratna Nugraheni (Prodi Akuntansi FEB UNITOMO, 2024)
The implementation of e-filing is said to be successful if there is an increase in the number of individual taxpayers who submit Tax Returns. The aim of this research is to obtain empirical evidence of the quality of the e-filing system, perceived convenience as well as security and confidentiality which are an important part of state tax revenues. The research sample is individual taxpayers. The sampling technique uses non-probability sampling using purposive sampling in sampling. The sample size is 100 individual taxpayers by sampling using a questionnaire. The analysis technique uses Multiple Linear Regression. The Adjusted R2 value of the multiple linear regression model is 52.3%. The results of the hypothesis test show that the quality of the e-filing system, perceived ease, security and confidentiality of e-filing have a significant effect on individual taxpayer compliance.